2020
DOI: 10.24820/ark.5550190.p011.314
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic strategies in curcumin chemistry focused on anticancer applications

Abstract: In spite of having received considerable interest as a potential anticancer agent over the past two decades, curcumin has not been developed into a sturdy drug candidate yet, mainly due to the challenges imposed by its rapidly metabolizable structure, leading to bioavailability and stability issues, and its aspecific activity. To circumvent these obstacles, chemical modification of the parent scaffold has been shown to involve an eligible approach for the construction of curcuminoids with improved properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 155 publications
0
6
0
Order By: Relevance
“…According to Table 3, the molecular weight of the analogous 3, 4, and 6 ranged from 343.25 to 434.36 g/mol, the amount of HBA ranged from 1 to 2, the amount of HBD ranged from 0 to 1 and the log P value ranged from 4.33 to 5.66. While the curcumin analogue 4 met the Lipinski Rules of Five, the analogues 3 and 4 violated one parameter of log P. Chander et al [31] also stated that 95% of clinically approved drugs had the following range of physicochemical properties: molecular weight (130-725), HA (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), HD (0-6) and log P (−2 to 6.5). Therefore, all the analogous 3, 4, and 6 met the physicochemical properties as stated in the previous study [31].…”
Section: Prediction Of Admet Parameters Of Curcumin Analogousmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Table 3, the molecular weight of the analogous 3, 4, and 6 ranged from 343.25 to 434.36 g/mol, the amount of HBA ranged from 1 to 2, the amount of HBD ranged from 0 to 1 and the log P value ranged from 4.33 to 5.66. While the curcumin analogue 4 met the Lipinski Rules of Five, the analogues 3 and 4 violated one parameter of log P. Chander et al [31] also stated that 95% of clinically approved drugs had the following range of physicochemical properties: molecular weight (130-725), HA (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), HD (0-6) and log P (−2 to 6.5). Therefore, all the analogous 3, 4, and 6 met the physicochemical properties as stated in the previous study [31].…”
Section: Prediction Of Admet Parameters Of Curcumin Analogousmentioning
confidence: 99%
“…Curcumin is one of the natural compounds that has been reported to have many bioactivities such as anticancer, antidiabetic, anti-inflammatory, antiviral, antimicrobial, antioxidant, and antiplasmodium [3]. A previous study showed that curcumin extract has good in vitro antiplasmodium activity with an IC 50 value of 3.5 μg/mL [4].…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 123–126 ] Synthetic manipulations on curcumin to obtain curcumin based heterocyclic compounds via MCR approach generates the molecules of enhanced therapeutic potential. [ 127 ]…”
Section: Pharmacological Activities Of Curcumin‐based Heterocycles Vi...mentioning
confidence: 99%
“…[123][124][125][126] Synthetic manipulations on curcumin to obtain curcumin based heterocyclic compounds via MCR approach generates the molecules of enhanced therapeutic potential. [127] Sahu et al [42] reported curcumin-based 4H-pyrimido [ 4) displays potent activity against fungal and bacterial strains. [53] The antibacterial activity of compounds 56 (MIC: 30.8 µM/mL), 58 (MIC: 28.6 µM/mL), 59 (MIC: 25.7 µM/mL), and 62 (MIC: 28.5 µM/mL) were most active against bacterial strain Bacillus cereus as compared to standard drug ampicillin (MIC: 38 µM/mL).…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%